Dokumen dalam Perspektif Ilmu Komunikasi - Yudhawasthi, Ciwuk Musiana (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2023)
ABSTRACT The definition of a document has changed quite significantly over time. The meaning of document has become increasingly widespread, not only for inanimate two- and three-dimensional objects but also includes living three-dimensional objects. In 1992 Blasius Sudarsono formulated an axiom which initially aimed to explain the library phenomenon from the perspective of Communication Science. This axiom is now used by Sudarsono as the axiom of